Pengaruh Produk, Citra, dan E-WOM Daya Tarik Wisata terhadap Keputusan Berkunjung ke Daya Tarik Wisata Pantai Melasti, Bali - Putri, Ni Putu Tita Kharisma Purnama; Bhaskara, Gde Indra (JURNAL DESTINASI PARIWISATA, 2023)
This study aims to analyze the influence of tourism product, destination image, and E-WOM on the visiting decision to visit Melasti Beach Tourist Attraction. The study attempts to describe the effect of these independent variables partially and simultaneously on the dependent variable. These three variables are some of the main factors that determine the decision making to visit a tourist attraction nowadays. This research itself is a mixed method using an embedded design with a correlation approach. The main data in this study is quantitative data with qualitative data as supporting data. The data collection techniques used in this study consisted of surveys, interviews, observation, and documentation. The population in this study were visitors of the Melasti Beach Tourist Attraction with a sample of 100 people taken by accidental sampling technique. The informants in this study were determined through a purposive sampling technique. The results of this study indicate that each variable, tourism product (X1), destination image (X2), and E-WOM (X3) have a positive and significant influence, both partially and simultaneously, on the visiting decision variable (Y). Based on the results of the correlation test, the independent variables have a very strong connection with the dependent variable, with a correlation coefficient (R) of 0.843. In general, the independent variables have 71% influence on the visiting decision variable. Keywords: tourism product, destination image, E-WOM, visiting decision